Does the prenatal bisphenol A exposure alter DNA methylation levels in the mouse hippocampus?: An analysis using a high-sensitivity methylome technique - Toshiki Aiba; Toshiyuki Saito; Akiko Hayashi; Shinji Sato; Harunobu Yunokawa; Toru Maruyama; Wataru Fujibuchi; Seiichiroh Ohsako (Genes and Environment, 2018)
Abstract Background There is still considerable debate about the effects of exposure to bisphenol A (BPA) an endocrine disrupter at low doses. Recently, many studies using animal models have shown that prenatal BPA exposure induces behavioral and neuronal disorders due to epigenetic changes in the brain. However, striking evidence of epigenomic changes has to be shown. Methods To investigate whether low-dose BPA exposure in the fetal stage can alter CpG methylation levels in the central nervous system, the hippocampus of the inbred C57BL/6 J mouse as the target tissue was collected to detect alterations in CpG methylation levels using a highly sensitive method of genome-wide DNA methylation analysis, methylated site display–amplified fragment length polymorphism (MSD-AFLP). Results BPA showed the sex-hormone like effects on male reproductive organs. Although we examined the methylation levels of 43,840 CpG sites in the control and BPA (200 μg/kg/day)-treated group (6 mice per group), we found no statistically significant changes in methylation levels in any CpG sites. Conclusions At least under the experimental condition in this study, it is considered that the effect of low-dose BPA exposure during the fetal stage on hippocampal DNA methylation levels is extremely small.